Perception of Medical Students in Cenderawasih University towards the Public Health Science Quetions of the Computer Based Test UKMPPD - Labobar, Maryam Kathrien; Liufeto, Koherista Gratia (Asian Journal of Healthcare Analytics, 2024)
This study aims to find out the perception of Medical students in Cenderawasih University towards the CBT UKMPPD Public Health Science problems. This research is qualitative research with a phenomenological design with data collection techniques, namely in-depth interviews and empirical observations to determine the theme. The themes found in this study are: 1) PH questions are classified as moderate-difficult, because the topic of PH Science is broad and not studied in depth, 2) Increasing practice of PH questions, 3) PH questions are confusing because they are rarely studied during education, 4) Topics that are considered difficult are research methodologies and national health insurance, 5) The time used to answer PH questions during the CBT is considered long because they have to remember the rules,  analyze and calculate, 6) Even though the presentation of questions is small, PH  questions affect the passing of CBT UKMPPD.